Determinants of Basic Immunization Uptake at the Medan Labuhan Community Health Center in 2025 - Eva Nirwana Natalia Hutabarat; Nurpaisa Nurpaisa (CV. Devitara, 2025)
This study aimed to analyze factors influencing the completeness of basic immunization among infants aged 0–12 months at Puskesmas Medan Labuhan in 2025. A quantitative cross-sectional design was applied involving 44 mothers selected through total sampling. Data were collected using structured questionnaires and verified with immunization records. Variables included maternal knowledge, family support, social environment, and immunization completeness. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. The results showed that maternal knowledge (p = 0.003; OR = 15.0), family support (p = 0.012; OR = 10.5), and social environment (p = 0.021; OR = 5.0) were significantly associated with immunization completeness. Strengthening education and community-based interventions is essential to improve immunization coverage.